CRITICAL THINKING PROCESS IN SCIENCE LEARNING - Halim, Lilia; Mokhtar, Lilia Ellany (Prosiding SNPS (Seminar Nasional Pendidikan Sains), 2015)
Critical thinkingÂ  is seen as an important competency for academic and career success. In the context of science education, critical thinking is important in order to be an effective citizen in the globalized world powered by rapid scientific and technological development. This paper begins by reviewing the literature on what is science (knowledge and practices), and why critical thinking is important in science learning. The paper then draws on a few studies to demonstrate that critical thinking has two main components knowledge and skills. Also on how to develop components of critical thinking skills effectively. This paper also argues that critical thiking process can only be critical when it is developed with scientific attitude.